Influence of active component cooling on process speed and joint strength during continuous induction joining of glass fiber reinforced polyamide 6 and steel: Einfluss einer aktiven Bauteilkühlung auf die Prozessgeschwindigkeit und die Fügefestigkeit beim kontinuierlichen Induktionsschweißen von glasfaserverstärktem Polyamid 6 und Stahl. Issue 11 (17th November 2016) - Hümbert, M.; Mitschang, P.
Abstract : Induction welding of metals and thermoplastic fiber reinforced polymer composites is a promising technology for the joining of hybrid components. It uses the possibility to induce eddy currents into a metal in order to melt the polymer of the adjacent composite. By applying pressure onto both parts, for example with a consolidation roller, the polymer adheres to the metal and a bond is generated. However, the relatively low process speed, caused by a slow cooling of the components, prevents a wide use of this method so far. Therefore, this study examines the influence of an active component cooling on the process speed and the resulting effects on the joining strength.